Study of TORCH infections and its impact on newborn babies and infants: a retrospective study in a tertiary care hospital in Visakhapatnam, Andhra Pradesh, India - Chilakala, Sai Prabha; P., Appa Rao; K., Ramalakshmi; Chaduvula, Suresh Babu (International Journal of Research in Medical Sciences, 2020)
Background: TORCH is an acronym for Toxoplasma, others (syphilis), Rubella, Cytomegalovirus and Herpes simplex virus. These are important causes of morbidity and mortality in new-borns, infants and children. Early diagnosis and treatment are essential to reduce the morbidity and mortality. Methods: It was a cross sectional record based retrospective record-based study conducted in King George Hospital, Andhra Medical College, Visakhapatnam, Andhra Pradesh. Samples from clinically suspected cases (newborns and infants) for possible TORCH infections were tested in virology laboratory from January to November 2019 and the samples were collected and tested by EUROIMMUN kit for the respective IgM antibodies and analyzed. Clinical details of newborns and infants were gathered from the patients through telephonic communication. Results: Total number of patients tested were 104 in which 54 (52%) showed positivity in which 36 were positive for CMV, 25 for HSV2, 23 for Rubella, 12 for Toxoplasma and 11 for Varicella zoster infection. Out of 52 positive cases 20.4% were alive and normal, 20% were alive but severely affected, mortality was 16.7%. Out of 16.7% mortalities 22% of deaths were due to nephrotic syndrome. Clinical manifestations include hepato-splenomegaly in 33.3% cases, fever in 30%, low birth weight in 25%, heart disease in 13.7%, microcephaly in 13.7%. Conclusions: Our study showed hepatomegaly, fever and low birth weight as common clinical manifestations. Fever and nephrotic syndrome were typically associated with CMV positive cases. Out of 52 % positively tested cases CMV was very common infection followed by HSV2, Rubella and Toxoplasmosis.